Determination of the anticancer activity of standardized extract of Centella asiatica (ECa 233) on cell growth and metastatic behavior in oral cancer cells - Suwisit Manmuan; Sukannika Tubtimsri; Nattaya Chaothanaphat; Nipatha Issaro; Mayuree H. Tantisira; Ponwit Manmuan (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: The anticancer drugs used for oral cancer treatment present many disadvantages, such as low solubility, low permeability, and poor bioavailability. However, the anticancer activity of ECa 233 has not been widely studied. Therefore, the anticancer activity of ECa 233 was investigated in this study. Experimental approach: MTT assay was carried out to determine cell viability. Characterizations of cell apoptosis were monitored using DAPI and FDA staining and Hoechst 33258 and AO staining. Confirmation of the apoptosis-induced KON cells was done using annexin V-FITC staining, and ROS generation was determined by DCFDA staining. Cell death and the cell cycle arrest activity of ECa 233 were demonstrated by a flow cytometer. The anti-migration and anti-invasion properties of ECa 233 were examined. The anti-proliferative of ECa 233 was investigated. Cellular uptake of ECa 233 was measured by TEER values. The pharmacokinetics of ECa 233 were estimated using the pkCSM web server. Findings/Results: ECa 233 decreased the KON cell viability. Morphological analysis showed the KON cells' loss of cell stability and structure, disorganized nucleus and cytoplasm, and induced cell death. ECa 233 acted as a cell cycle arrest in the G0/G1 phase and reduced the migration and invasion ability in KON cells. TEER values significantly increased in KON cells, which decreased cell colony and multicellular spheroid formations. The pharmacokinetic profiles of the main components are of interest for future usage. Conclusion and implication: ECa 233 can be used as an alternative therapy as well as a medicinal plant selected for sensitizing oral cancer cells to chemotherapy.